2012
DOI: 10.1007/s00198-012-2154-z
|View full text |Cite
|
Sign up to set email alerts
|

Incidence of hip fractures in Greece during a 30-year period: 1977–2007

Abstract: The incidence of hip fractures doubled during the last 30 years among people aged ≥50 years, although a mild decrease was observed in almost all age groups after 2002. The most affected group is 80 and over.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
15
1
2

Year Published

2014
2014
2017
2017

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 31 publications
(19 citation statements)
references
References 22 publications
1
15
1
2
Order By: Relevance
“…This tendency is similar in other countries [1012]. As evident in group under 80 years, there is no increase in the number of fracture.…”
Section: Discussionsupporting
confidence: 87%
“…This tendency is similar in other countries [1012]. As evident in group under 80 years, there is no increase in the number of fracture.…”
Section: Discussionsupporting
confidence: 87%
“…A further validation is the external replication of reversals in studies not included, e.g. outside of the European region 43, 44 or using alternative methodological approaches 45 . Regarding the effect of age, we opted to use categories as defined in each publication and their midpoint as the index age.…”
Section: Discussionmentioning
confidence: 99%
“…(47) More recent national data showed stable rates in men and women between 2002 and 2008. (48) A recent trend study from Greece, (49) collecting data by a questionnaire sent to all public and private orthopedic departments for the years 1997, 2002, and 2007, compared the ageadjusted hip fracture rates to those reported by a previous study (50) The accuracy of the data was difficult to assess because they were collected by questionnaire without using the International Classification of Diseases (ICD) code to define fractures, and incidence rates were limited to selected years rather than the entire time period. Comparison of two incidence studies from Turkey suggests a substantial increase in hip fracture rates over a 20-year period.…”
Section: Southern Europementioning
confidence: 99%
“…(47) More recent national data showed stable rates in men and women between 2002 and 2008. (48) A recent trend study from Greece, (49) collecting data by a questionnaire sent to all public and private orthopedic departments for the years 1997, 2002, and 2007, compared the ageadjusted hip fracture rates to those reported by a previous study (50) for the years 1977, 1982, 1987, and 1992. It showed that rates increased significantly between 1977 and 2002 (3.3%/year in men and 4.9%/year in women) but later stabilized in men and decreased in women by 1.5%/year between 2002 and 2007.…”
Section: Southern Europementioning
confidence: 99%